Tamsulosin in the treatment of urological disorders - a literature review - Kaczmarek, Błażej; Kruk, Adrian; Dorosz, Aleksandra; Skoczeń, Agnieszka; Kulesza, Michał; Wawrzynów, Weronika; Jakubowska, Magdalena Maria; Rutecka, Natalia; Miłoś, Martyna; Kuśnierz-Gibała, Agata (Journal of Education, Health and Sport, 2025)
Benign prostatic hyperplasia (BPH) is one of the most common diseases in the elderly, affecting almost half of men over 50 years of age and nearly 90% of men over 80 years of age. The most common complication of BPH is acute urinary retention, which significantly reduces the quality of life of patients. Pharmacological treatment with alpha blockers and 5-alpha reductase inhibitors is the first line of therapy for BPH. Tamsulosin, as a selective alpha-1 receptor antagonist, is one of the preferred alpha blockers due to its relatively lower side effects compared to other drugs in this class. Tamsulosin has linear pharmacokinetic properties and its absorption is sensitive to the presence of food. The purpose of one study was to evaluate the efficacy and safety of a double dose of tamsulosin (0.8 mg) in patients with BPH who did not respond to the standard dose (0.4 mg) and were not candidates for transurethral intervention. An open-label, randomized, three-stage study included 111 patients who experienced severe symptoms of BPH. Before and after one month of treatment, several parameters were evaluated, including the International Prostate Symptom Score (IPSS), prostate-specific antigen (PSA) level, prostate volume, maximum urine flow (Qmax) and post-void urine volume. The results of the study showed that all the patients were treated and the mean age of the participants was 63.12 ± 4.83 years. Improvements in Qmax, post-void urine volume and IPSS score were observed in 93 patients (p < 0.001). Total IPSS and Qmax improved from 24.03 ± 2.49 to 16.41 ± 3.84 and from 7.72 ± 1.64 to 12.08 ± 2.37 ml/s, respectively. Finally, a double dose of tamsulosin 0.8 as an alpha-blocker therapy: an effective treatment option for patients with BPH who have failed to respond to standard therapy and who are not candidates for surgical intervention.